E-education in the Philippines: The case of technical education and skills development authority online program - Madeline Dumaua-Cabauatan; Sylwyn C. Calizo; Francis Mark A. Quimba; Lachmi C. Pacio (Philippine Institute for Development Studies (PIDS), 2018)
Education and training for productive employment play a crucial role in the social and economic plans of a developing country like the Philippines. Technical and vocational education and training (TVET) in the country has been viewed as a tool to help equip the people with the necessary skills for employment. In effect, this increases their income potential, and eventually, remove them from poverty. To reach more people, more so, those in the remotest places, TESDA introduced information, communications, and technology (ICT) into TVET and launched the TESDA Online Program (TOP) in 2012. TOP is the first Philippine institution to offer massive open online courses. Current TESDA statistics estimate that more than a million Filipinos were able to access and utilize the TOP. This study assesses how ICT has enabled the Filipinos to have access and use online technical education offered free by e-TESDA program. It also acknowledges the unlimited opportunities offered by TOP through its courses and the potential number of users/beneficiaries. The vision of a globally competent Filipino workforce with advanced skills can be realized with the encouraging results of the TOP accreditation and certification. Read more about the recommendations on how to improve the current TOP in this study.
Keywords: 330; Philippines; digital economy; TVET; e-education; e-learning; technical and vocational education and training; Technical Education and Skills Development Authority; TESDA; information and communications technology; digital literacy